Ensaios farmacológicos clínicos com o extrato das raízes do Panax ginseng C. A. Meyer no controle da ansiedade - Braga, João Euclides Fernandes (2011)
Anxiety is an adaptive response of organism to situations that life presents, and driving performance with personal and psychological as well as physiological components. It is considered pathological when it causes suffering to the individual, bringing him damage in terms of injury avoidance behaviors and avoidance important situations in his academic, social and professional life. The pathological manifestations of anxiety are grouped as Anxiety Disorders. Several pharmacological classes are used to treat this group of disorders, especially benzodiazepines and antidepressants. However, the pattern of adverse reactions, the possibility of tolerance and dependence as well as abuse potential of benzodiazepines, added to slow response of antidepressant treatment, justify the search for new therapeutic possibilities. Preclinical studies have attested the anxiety-relieving activity of the roots extract of Panax ginseng C. A Meyer. Its ethnopharmacological use for anxiety is evident worldwide. The aim of this study was to test the therapeutic efficacy of the extract of the roots of P. ginseng in the acute treatment of experimentally induced anxiety in healthy volunteers and identify adverse effects caused by its use. The study population consisted of university students, aged between 18 and 30 years. We selected 60 healthy volunteers who met the study inclusion criteria. We developed a clinical double-blind, randomized, controlled, acute essay. The substances used were: P. ginseng (200 mg), diazepam (10 mg) and placebo. Anxiety was experimentally elicited through Simulation Test of Public Speaking, and evaluated through the use of physiological measures (blood pressure, heart pulse rate, ends temperature and skin electrical conductance) and psychometric scales (trait-state anxiety inventory and analog mood scale). The results were analyzed using several statistical, parametric and nonparametric methods. They showed that the extract of the roots of P. ginseng intensifies anxiety, especially during performance test and has a minor ability to reduce it in the final phase, with greater significance demonstrated through psychological measures. Although well tolerated, P. ginseng has not demonstrated effectiveness in controlling anxiety and subjective signs and symptoms associated with it.